2016
DOI: 10.4254/wjh.v8.i23.985
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of multidrug resistance of hepatocellular carcinoma cells by metformin through inhibitingNF-κBgene transcription

Abstract: AIM:To interfere with the activation of nuclear factor-κB (NF-κB) with metformin and explore its effect in reversing multidrug resistance (MDR) of hepatocellular carcinoma (HCC) cells. METHODS:Expression of P-glycoprotein (P-gp) and NF-κB in human HepG2 or HepG2/adriamycin (ADM) cells RESULTS: P-gp overexpression in HepG2 and HepG2/ ADM cells was closely related to mdr1 mRNA (3.310 ± 0.154) and NF-κB mRNA (2.580 ± 0.040) expression. NF-κB gene transcription was inhibited by specific siRNA with significant down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
0
19
0
1
Order By: Relevance
“…In the present study, it was confirmed that the chemo-refractory phenotype was reversed by EGb 761 by suppressing NIBP, the NF-κB signaling pathway and EMT. Research suggests that the activation of NF-κB weakens the effects of chemotherapy drugs on tumor cells and that it is associated with enhanced multi-drug resistance (23,24). Furthermore, cisplatin results in acquisition of chemoresistance via triggering EMT through the NF-κB signaling pathway (12,25).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was confirmed that the chemo-refractory phenotype was reversed by EGb 761 by suppressing NIBP, the NF-κB signaling pathway and EMT. Research suggests that the activation of NF-κB weakens the effects of chemotherapy drugs on tumor cells and that it is associated with enhanced multi-drug resistance (23,24). Furthermore, cisplatin results in acquisition of chemoresistance via triggering EMT through the NF-κB signaling pathway (12,25).…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al first described that a combination of tamoxifen and cyclosporin A showed significant synergism on the sensitivity to doxorubicin of both low and high ABCB1-expressing HCC cell lines [ 16 ]. Recently, Wu et al also reported that metformin, by silencing NF-κB signaling, could effectively reverse MDR in HCC cells by the downregulation of ABCB1 expression [ 17 ]. Even though these strategies show some positive effects on MDR reversal, the innate toxicities of these compounds, for example, off-target effects from antisense RNA constructs, and severe side effects caused by these compounds must be carefully considered [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, several studies have reported that metformin not only inhibits cell proliferation in breast, gastric, ovarian, and small cell lung cancers [8][9][10][11] but also potentiates the cytotoxic effect of some TKIs in bladder, colorectal, and non-small cell lung cancer [12][13][14]. In addition, it is also known to reverse multidrug resistance by regulating cancer stem cell population or signaling [15][16][17]. However, the effects of metformin on CML have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%